(3eTQhYjI GdGYJbGd GdEOGQj aj GdXQha GdGSJKfGFjI (B: s (3OQGSI oebGQfI (B/ s - (3gGja fGUQ gGja GdMhjdI s; (3SYGO GdTQbGhi (B: s ((3GdbGgQI (B: s (3cdjI GdMbhb , LGeYI GdbGgQI(B: s, 2014)
(3EPG cGf NVhY GdOhdI deHOC GdeTQhYjI gh GdbGYOI GdhGLH GMJQGegG aj Xd GdXQha GdYGOjI(B: (3aEf GdOhdI bO JeQ HXQha GSJKfGFjI ef TCfgG Cf JTcd NWQG Ydi GdfXGe GdYGe Ch GSJeQGQjI NOeGJ GdeQGab GdYGeI(B: (3hdehGLgI gPG GdNWQ(B: (3aEf SdWGJ GdEOGQI bO JJSY(B. (3aGdQZHI aj MeGjI GdOhdI hGdMaGX Ydi GdfXGe GdYGe ajgG VO eG bO jgOOgG ef CNWGQ LSjeI(B: (3COJ HGdeDSS GdOSJhQj Ch GdeTQY GdYHGOj Edi GdGYJQGa ddEOGQI HGJNGP ELQGAGJ GSJKfGFjI dehGLgI Jdc GdCNWGQ(B. (3hef Hjf GdELQGAGJ GdGSJKfGFjI GdJj jLhR ddOhdI Cf JJNPgG aj Xd GdXQha GdGSJKfGFjI (B((3ELQGA GdGYJbGd(B) (3haj gPg GdUOO dG jecf aUd GdGYJbGd Yf LPhQg GdeJeKdI aj GdbhGfjf GdJTQjYjI hGdYQajI(B: (3aGdGYJbGd ef CbUi GdELQGAGJ GdJj bO JUjH MjGI GdaQO hCKQg jeJO Edi LejHY GdMbhb hGdMQjGJ GdNGUI HGdCaQGO h ef Ke abO YQaJ ai gPG GdHMK GdJWhQ GdJGQjNi ddGYJbGd(B. (3h GdeYGjjQ GdOhdjI dEYdGf MGdI GdWhGQF(B. (3h CfhGY GdhKGFb GdOhdjI GdNGUI HMbhb GdEfSGf s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe (B2014s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOSJhQjs; (3GdGYJbGd GdEOGQjs; (3GdXQha GdGSJKfGFjIs; (3GdhKGFb GdOhdjI GdNGUI HMbhb GdEfSGfs; (3QSGFd LGeYjIs -- (3GdbGgQIs -- (3cdjI GdMbhbs